Forest Tenure and Sustainable Forest Management: Drawing Lessons from the Literature - Sarfo-Adu, Gordon Kofi (Environmental Management and Sustainable Development, 2021)
The quest to foster sustainable forest management (SFM) in the era of sustainable development goals has reignited the debate on forest tenure concerns. Land and forest tenure insecurity has remained a major underlying cause of deforestation in Africa, which suggests that addressing tenure issues could effectively foster sustainable forest management. Adopting theoretical literature and drawing lessons from related empirical works, this study examines the role of land and forest tenure in sustainable forest management drive. Among other things, the study discusses how land tenure promotes or inhibits sustainable forest practices. The study outlines how frustrating tenure regimes deprive the community of the needed benefits and subsequent untoward behaviour unleashed on forests. The study concludes that the idea of tenure rights and tenure security has implications on sustainable forest management and admonishes a robust tenure regime that upholds local 'people's access to and usage of forest resources without sinister machinations and subjugation of local people. The study contends that determined rights and their long-term security remain crucial in attracting the tenure holders to make a strenuous investment in SFM since investments in forestry usually are made for the long term. Among other things, the study recommends for clarity and long-term security of ownership and tenure rights regarding forest products; a need to promote capacity-building for administrators and rights holders to adopt a sustainable mindset in their exploitation of timber products; and a need to foster stakeholder participation.